Guide to the Madrid system : International Registration of Marks under the Madrid Protocol (World Intellectual Property Organization, 2022)
Guide is primarily intended for applicants and holders of international registrations of marks, as well as officials of the competent administrations of the Member States of the Madrid Union. It leads them through the various steps of the international registration procedure and explains the essential provisions of the Madrid Agreement, the Madrid Protocol and the Common Regulations.
Keywords: Trademarks (International law); Marques de commerce (Droit international)